Focus and impact on climate change adaptation and mitigation - CGIAR Initiative on NEXUS Gains (International Water Management Institute, 2024)
A NEXUS Gains impact area brief shares how the Initiative’s five work packages aim to mitigate and adapt to climate change by creating co-benefits and reducing trade-offs among water, energy, food, and ecosystems in highly vulnerable river basins.